Analisis SWOT Rumah Sakit Islam Ibnu Sina Simpang Empat YARSI Sumatera Barat - Meri Herliza; Yusmia Rahdiani (Pusat riset dan Inovasi Nasional, 2025)
This research aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) and find out the marketing strategies that can be carried out by Ibnu Sina Islamic Hospital Simpang Empat. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, interviews with hospital management and staff, and documentation studies. The results of the SWOT analysis showed that Ibn Sina Simpang Empat Islamic Hospital has a strategic location, and has been accredited with 5-star plenary twice. Weaknesses found include not having a complete permanent doctor, not being able to refuse policies from the Regional Government, limited hospital land making it difficult to develop, difficult to make strategic policies related to human resources and finance. medical services that are not updated and others. Opportunities that can be utilized include the many opportunities for cooperation with other companies, the only private general hospital in West Pasaman, a strategic location in the government area, the population of the West Pasaman community of around 441,773, a fairly good community economy, the UHC (Universal Health Coverage) system from the government, and Yarsi branding. Based on the results of the SWOT analysis, this study recommends several strategies to improve the competitiveness of the Ibn Sina Simpang Empat Islamic Hospital, namely with aggressive strategies such as improving financial management, strengthening promotion and marketing, developing the competitiveness of the hospital.